ANALISIS KINERJA KEUANGAN PT. “A” INDONESIA TAHUN 2007 – 2012 - Chairina Utami; Djuma hir (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to identify and analyze financial performance of PT. “A” Indonesia in 2007 - 2012 assessed by the ratio of liquidity, solvency, profitability, and activity. This study is a descriptive analysis research by using a quantitative approach. This study uses quantitative data as the only type of data. Based on the source, the data used in this study is primary data, the data obtained directly from the PT.